Hubungan Pengetahuan Ibu Menyusui dengan Pemberian ASI Ekslusif di BPM Siti Fujana Kabupaten Aceh Timur Provinsi Aceh Tahun 2024 - Siti Mustika Zahara; Friza Novita Sari Situmorang; Ingka Kristina Pangaribuan; Parningotan Simanjuntak; Rismalia Tarigan (Lembaga Pengembangan Kinerja Dosen, 2025)
Breast milk (ASI) is the first, main and best food in the early stages of a baby's life that is natural. ASI is like gold given for free by God because ASI is a living fluid that can adjust its substance content that can meet the nutritional needs of babies. Based on data from the World Health Organization (WHO) until 2020, only around 44% of babies worldwide aged 0-6 months received exclusive ASI. This is not in accordance with the WHO target in 2025, which is to increase the provision of exclusive ASI in the first 6 months to at least 50% (WHO, 2020). The coverage of exclusive ASI according to Regency/City in 2022 can be seen from the data reported by Central Aceh Regency with the highest coverage of 82.34% and the lowest is Sabang City at only 22.43%. This study aims to identify the Relationship between Knowledge of Breastfeeding Mothers and Exclusive Breastfeeding at BPM Siti Fujiana, East Aceh Regency in 2024. This study used a Cross Sectional design, the research time was May-June 2024, with a population and sample of 46 people. The sampling technique used total sampling, the analysis test used the Chi Square Test. The majority of respondents were aged 20-35 years as many as 26 respondents (56.5%), the majority of respondents had secondary education (junior high school-high school) as many as 32 respondents (69.6%), the majority of respondents did not work as many as 37 respondents (80.4%), and the majority of breastfeeding mothers with grandemultipara status as many as 27 respondents (58.7%). There is a significant relationship between Knowledge of Breastfeeding Mothers and Exclusive Breastfeeding at BPM Siti Fujiana, East Aceh Regency with a p value <0.05 (0.003). This means that the better the mother's knowledge, the more Exclusive Breastfeeding will be implemented.